2001
DOI: 10.1002/1096-8652(200103)66:3<189::aid-ajh1043>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Rare adult acute lymphocytic leukemia with CD56 expression in the ECOG experience shows unexpected phenotypic and genotypic heterogeneity

Abstract: Expression of CD56, a marker of natural killer (NK) cells, in acute lymphocytic leukemia (ALL) is rare and, to date, has been described only in non-B lineage ALL. Among 194 patients with CD56 analysis on the ongoing Eastern Cooperative Oncology Group (ECOG) ALL trial, E2993, 6 cases of CD56+ ALL were found (3.1%) with a median of 95% of blast cells expressing CD56, compared with a median of 1% of blast cells in CD56- ALL (P = 0.0001). FAB-L2 characteristics dominated, without granulation. Blast cells from four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 38 publications
(69 reference statements)
3
14
2
Order By: Relevance
“…The frequency of aberrant myeloid antigen expression in the studied ALL group was 36.4%, our results are in accordance to 39% reported by Bhushan et al (2010), comparable to 21.2% (Paietta et al, 2001), and 55% reported by Wu et al (2007), while in contrast to others references (Pui et al, 1998;Vitaleet al, 2007).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leusupporting
confidence: 91%
See 2 more Smart Citations
“…The frequency of aberrant myeloid antigen expression in the studied ALL group was 36.4%, our results are in accordance to 39% reported by Bhushan et al (2010), comparable to 21.2% (Paietta et al, 2001), and 55% reported by Wu et al (2007), while in contrast to others references (Pui et al, 1998;Vitaleet al, 2007).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leusupporting
confidence: 91%
“…In this work, CD56 was detected in 9% in ALL, mildly lower frequency of CD56 expression were reported earlier; 5% (Seegmiller et al, 2009), 3% (Paietta et al, 2001) and 2.2% (Hussein et al, 2011). We reported 4 cases with hyperdiploidy all were expressing CD34 and two of them lost CD45 in agreement with others who found higher CD34 expression in B-ALL with hyperdipolidy and under expression or loss of CD45 (Behm et al, 1992;Seegmiller et al, 2009).…”
Section: 221 Clinical Significance Of Aberrant Antigens In Acute Leusupporting
confidence: 90%
See 1 more Smart Citation
“…[5][6][7] In T-cell acute lymphoblastic leukemia/lymphoma (T-ALL/LBL) CD56 expression has been reported for a small number of cases and an association with worse outcome has been suggested. [8][9][10][11] The expression of other single antigens such as CD2, CD10 or myeloic antigens has been evaluated for their prognostic impact in T-ALL. [12][13][14] However, the immunological subtype is still the leading prognostic factor, with thymic T-ALL having a considerably better prognosis than pre-T or mature T-ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of nonnasal NK-cell lymphomas occurring in the skin or soft tissue from extramedullary AML is particularly important for prognostic and therapeutic decisions. However, in acute lymphoblastic leukemia CD56 expression is relatively rare 134,[145][146][147] . CD56 is also expressed in a subset of T-cells, as well as 5-20% of peripheral T-cell lymphomas [148][149][150][151][152][153] .…”
mentioning
confidence: 99%